Kiat Mendidik Shalat Anak Berkebutuhan Khusus dan Relevansinya Bagi Kesehatan Mental Anak Berkebutuhan Khusus (Studi Analisis Buku â€œAku Abk, Aku Bisa Shalatâ€ Karya Muhammad Yamin Muhtar) - Astutik, Sri Puji; Mufid, Mufid (Tunas Nusantara, 2023)
Prayer education is a parent's obligation to begin before the child reaches puberty. This does not only apply to children with normal abilities and growth but also to children with special needs. To capture the material being taught, ABK needs tips for teaching prayer that are appropriate to their age development. This type of research is library research. The primary data source is the book Aku ABK, Aku Can Pray, secondary data comes from books and other relevant research. The results of the research show that tips for educating children with special needs to pray according to Muhammad Yamin Muhtar in the book Aku ABK, I Can Pray are (a) Introduction to prayer for ABK (b) Teaching ABK prayers through remedial methods (c) Parents as role models (d) characteristics what parents need to have: patience, always full of hope and prayer, etc. (e) Initial preparation: providing a special time, special place, preparing prayer equipment, preparing gifts. (f) Stages and Methods: Accompaniment, independence, independence, and refinement and improvement stages (g) Delivering concise prayer readings (h) Creating a good environment (i) Praying for children (j) Fostering sincerity in prayer. The relevance of prayer for the mental health of crew members is that it can train focus and concentration, increase brain intelligence, as social therapy, and increase interpersonal sensitivity.